2012
DOI: 10.1371/journal.pone.0038029
|View full text |Cite
|
Sign up to set email alerts
|

Active Zone Protein Bassoon Co-Localizes with Presynaptic Calcium Channel, Modifies Channel Function, and Recovers from Aging Related Loss by Exercise

Abstract: The P/Q-type voltage-dependent calcium channels (VDCCs) are essential for synaptic transmission at adult mammalian neuromuscular junctions (NMJs); however, the subsynaptic location of VDCCs relative to active zones in rodent NMJs, and the functional modification of VDCCs by the interaction with active zone protein Bassoon remain unknown. Here, we show that P/Q-type VDCCs distribute in a punctate pattern within the NMJ presynaptic terminals and align in three dimensions with Bassoon. This distribution pattern o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(95 citation statements)
references
References 55 publications
5
90
0
Order By: Relevance
“…We labelled NMJs with antibodies to three AZ markers: bassoon (encoded by Bsn), piccolo (encoded by Pclo) and P/Q VGCC (specifically the subunit encoded by Cacna1a). In WT mice, these proteins presented with a clear punctate staining (Nishimune et al, 2012) (Fig. 2A-C), but the fluorescence intensity of these three markers was drastically reduced in both integrin-α3 +/− and integrin-α3 −/− NMJs ( Fig.…”
Section: Integrin-α3 Is Concentrated At the Azs Of Nmjs And Regulatesmentioning
confidence: 99%
See 1 more Smart Citation
“…We labelled NMJs with antibodies to three AZ markers: bassoon (encoded by Bsn), piccolo (encoded by Pclo) and P/Q VGCC (specifically the subunit encoded by Cacna1a). In WT mice, these proteins presented with a clear punctate staining (Nishimune et al, 2012) (Fig. 2A-C), but the fluorescence intensity of these three markers was drastically reduced in both integrin-α3 +/− and integrin-α3 −/− NMJs ( Fig.…”
Section: Integrin-α3 Is Concentrated At the Azs Of Nmjs And Regulatesmentioning
confidence: 99%
“…In vitro expression studies demonstrate that bassoon positively regulates the activity of the P/Q VGCC, prolonging its opening times (Nishimune et al, 2012); therefore, the reduced localisation of bassoon at integrin-α3 +/− NMJs might cause a decreased influx of Ca 2+ at these terminals, which would be exacerbated when the concentration of external Ca 2+ is reduced. Given the deficiency of bassoon and piccolo at adult integrin-α3 +/− AZs (Fig.…”
Section: Role Of Integrin-α3 At the Azmentioning
confidence: 99%
“…Thus, P/Q-type VGCCs and the direct interaction with laminin-β2 are necessary for efficient organisation of active zone elements. This could be due to the closer localisation of P/Q-type to release sites, being more favourable in interaction with presynaptic components in comparison with N-type VGCCs which are localised further away from the release sites (Urbano et al, 2002;Nudler et al, 2003) despite both VGCCs having direct interaction with presynaptic proteins such as Bassoon, SNAP25 and Syntaxin 1A (Kim & Catterall, 1997;Zhong et al, 1999;Chen et al, 2011;Nishimune et al, 2012).…”
Section: Failure In Switching Of N-to P/q-type Vgcc Clusters At Maturmentioning
confidence: 99%
“…Multiple VGCCs sub-types coexist at a single synapse and interact to induce release of transmitter (Regehr & Mintz, 1994;Dunlap et al, 1995). P/Q-type VGCCs are spatially located in closer proximity to release sites compared to the more abundant N-type VGCCs Nudler et al, 2003;Urbano et al, 2003;Nishimune et al, 2012). This close spatial localisation may well be the reason P/Q-type VGCCs play a more prominent role in the mature junction where efficient bulk release of transmitter is required (Rosato-Siri et al,…”
Section: Laminin-β2 Deficient Neuromuscular Junctions Maintained Depementioning
confidence: 99%
“…Prior research has shown that the maintenance of active zone composition, and the molecular organisation of key components is strongly influenced by P/Q-type VGCCs (Nishimune et al, 2004;Nishimune et al, 2012). Previous research suggests that P/Q-type VGCCs interact directly with SNAP25 and syntaxin via the pore forming α-subunits, while Bassoon is capable of interacting with the β1b and β4 subunits of VGCCs (Kim & Catterall, 1997;Zhong et al, 1999;Chen et al, 2011;Nishimune et al, 2012).…”
Section: Structures As the Neuromuscular Junction Maturesmentioning
confidence: 99%